2023
DOI: 10.1002/mbo3.1384
|View full text |Cite
|
Sign up to set email alerts
|

A loophole in soap dispensers mediates contamination with Gram‐negative bacteria

Ralf Lucassen,
Nicole van Leuven,
Dirk Bockmühl

Abstract: Liquid soap dispensers are widely used in domestic and clinical settings. In previous studies, the risk of bacterial contamination of refillable systems was pointed out and a bacterial contamination rate of 25%, with values of up to 108 colony‐forming units/mL (CFU/mL), was reported. However, the route of contamination remains elusive. To address this point, we determined the microbial contamination of refillable standard pump dispensers and nonrefillable press‐dispenser systems. Following the collection of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…While many epidemiological studies report on the resistance rates of these pathogens globally, the data on rising rates of antiseptic and disinfectant resistance is scarce, however, these resistance mechanisms should be appreciated during IPC initiatives [ 17 ]. For example, it was shown that hands heavily contaminated (10 6 colony-forming units [CFU]/fingertip) with A. baumannii could survive the effects of many antiseptics and disinfectants, or that these bacteria could survive in soap dispensers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While many epidemiological studies report on the resistance rates of these pathogens globally, the data on rising rates of antiseptic and disinfectant resistance is scarce, however, these resistance mechanisms should be appreciated during IPC initiatives [ 17 ]. For example, it was shown that hands heavily contaminated (10 6 colony-forming units [CFU]/fingertip) with A. baumannii could survive the effects of many antiseptics and disinfectants, or that these bacteria could survive in soap dispensers [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%